The Effect of Increasing Compensation on Employee Work Motivation in Multi-Business Cooperatives Prima Grathia Prosperous Lombok - Sariman, Angelina; Lukitasari, Diah; Dianti, Ira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this research is to determine the effect of providing compensation on employee work motivation at the Prima Grathia Sejahtera Lombok Multi-Enterprise Cooperative. This research used quantitative methods with a sample size of 54 people. The research methods used are coefficient of determination and multiple linear regression. The results in this study prove that work compensation has a partially positive and significant effect on employee performance because the t-count of 4,933 is greater than the t-table of 2,009. Work motivation has a partially positive and significant effect on employees because the t-count is 4,933 and the t-count of 755 is greater. from t-table 2.009. Meanwhile, simultaneously the compensation variable has a positive and significant effect on employee motivation because the f-count value of 570 is greater than the f-table of 2.56.